In situ determination of the complex permittivity of ultrathin H2-infused palladium coatings for plasmonic fiber optic sensors in the near infrared. Issue 19 (1st May 2018) - Zhang, Xuejun; Cai, Shunshuo; Liu, Fu; Chen, Hao; Yan, Peiguang; Yuan, Yong; Guo, Tuan; Albert, Jacques
Abstract : In situ determination of the complex permittivity of H2 -infused palladium using near infrared plasmons over optical fibers. Abstract : The high price and volatile supply source of oil as well as the desire to move towards greener sources of energy have created a growing interest in the use of alternative fuels, such as hydrogen. It is vital to have an inexpensive device that can quickly, sensitively, reliably and safely monitor hydrogen concentrations in case there is a leak. In this paper, we report measurements of the complex permittivity of 7 nm thick palladium thin films exposed to concentrations of 0 to 3% (by volume) hydrogen in nitrogen at wavelengths near 1310 nm. Measurements were carried out with a tilted fiber Bragg grating first coated with 30 nm of gold and then palladium at several thicknesses between 3 and 43 nm. The tilt angle of the grating was fixed at 23 degrees in order to allow the excitation of surface plasmon resonances on the gold surface by high order cladding modes in air at wavelengths near 1310 nm. Simulations of the grating response based on measurable experimental parameters indicate that for palladium thicknesses between 3 and 10 nm, the measured changes in the grating transmission become independent of thickness. Therefore, for a 7 nm thick film, any change in transmission can be traced directly to changes in permittivity. The relative change of the permittivity of the palladium layer was found to scale linearly with hydrogen concentration with a scaling factor of −0.15/%H2 for hydrogen concentrations between 0 and 1.7%. The limit of detection of the grating configuration used was determined to be 380 ppm at three times the standard deviation for measurements averaged over 80 seconds. Using standard fiber optic instrumentation and a single mode fiber, the signal to noise ratio was over 100.